Effect of Fixed Adsorption Bed Structure on Regeneration and Dehumidification - Yang Lijun; Li Wei; Chen Linan; Zheng Qiao; Chen Wei (Zhileng xuebao, 2015)
A special fixed bed structure is introduced, in which DN20 water pipes pass through the fixed bed. Silica gel is used as solid adsorption materials of fixed bed, and water with different temperatures is supplied in the pipes in the experiment. The regeneration capacity and adsorption effect in the three experiment cases are compared by three evaluation indexes, i.e., dehumidifying capacity, adsorption capacity and energy efficiency ratio. Experiment 1 is best in regeneration capacity and adsorption effect. The analytical capacity of experiment 1 is 36% greater than experiment 2 and 12% than experiment 3. The dehumidification capacity of experiment 1 is 16% greater than experiment 2 and 17% than experiment 3.